Non-contrast-enhanced hepatic MR arteriography with balanced steady-state free-precession and time spatial labeling inversion pulse: optimization of the inversion time at 3 Tesla. (27th November 2015) - Kawahara, Seiya; Isoda, Hiroyoshi; Ohno, Tsuyoshi; Furuta, Akihiro; Togashi, Kaori
Background: A 3 Tesla (3 T) magnetic resonance (MR) scanner is a promising tool for upper abdominal angiography. However, no report has focused on the contrast behavior of non-contrast-enhanced hepatic MR arteriography at 3 T. Purpose: To establish the optimal inversion time (TI) for favorable selective visualization of the hepatic arteries on non-contrast-enhanced MR arteriography with time spatial labeling inversion pulse (Time-SLIP) at 3 T. Material and Methods: Twenty-five healthy volunteers were examined using respiratory-triggered three-dimensional balanced steady-state free-precession combined with Time-SLIP. According to the difference in the TI, five image groups (A, B, C, D, and E, from 1200 to 2000 ms, increasing at 200-ms intervals) were performed and compared to detect the optimal TI for hepatic artery visualization. The relative Cv-l (vessel-to-liver contrast) was quantified. For qualitative evaluation, the vessel visualization quality and order of the depicted hepatic artery branches were evaluated. Results: In group C (TI of 1600 ms), the Cv-l showed the highest probably due to a favorable balance between the hepatic vessel signal and signal recovery of the surrounding tissue. Regarding qualitative assessment, in group C, the mean image quality score of all hepatic arteries and mean maximal visible order of the hepatic artery branches were the highest. However, there was no significant difference between these results. Conclusion: Non-contrast-enhanced hepatic MR arteriography with Time-SLIP at 3 T enabled the selective visualization of hepatic arteries at a TI of 1600 ms with an optimal balance between Cv-l and peripheral hepatic artery visualization.